(untitled) (Research, Society and Development, 2024)
Objective: This review aims to examine the current scientific literature on the use of medicinal cannabis in the treatment of chronic pain, investigating the effects of cannabinoids, their efficacy, safety, mechanisms of action, and therapeutic potential. The goal is to contribute to a better understanding and clinical application of medicinal cannabis as a treatment option for patients with chronic pain. Methodology: A narrative literature review was conducted using data available in databases such as LILACS, PubMed, and BVS, crossing the descriptors "chronic pain," "cannabis," "medicinal cannabis," and "pharmacokinetics" in Portuguese, English, and Spanish. Results: The pathophysiology of chronic pain is complex, involving neural and neuroimmune interactions, and is associated with conditions such as stress, anxiety, and depression. Medicinal cannabis, especially CBD, demonstrates analgesic and anti-inflammatory potential, but further research is needed to confirm its efficacy and safety. Conclusion: The complexity of using cannabis compounds in the treatment of chronic pain is evident. Although there are promises regarding THC and CBD, there is still a lack of data on mechanisms, efficacy, and safety. A cautious approach, based on clinical studies and integrated into broader and more individualized treatment strategies, is essential to guide the clinical use of these substances.